INTEGRATING EVIDENCE-BASED MEDICINE INTO MEDICAL EDUCATION: ENHANCING CLINICAL DECISION-MAKING AND PATIENT CARE (World Bulletin of Public Health, 2025)
Evidence-Based Medicine (EBM) has become a cornerstone of modern healthcare, ensuring that clinical decisions are guided by the best available scientific evidence. Integrating EBM principles into medical education is essential for fostering critical thinking, improving clinical reasoning, and enhancing patient outcomes. This paper explores the role of EBM in medical curricula, emphasizing its impact on clinical decision-making and patient care. Effective EBM education involves teaching students how to critically appraise research, apply relevant findings to patient cases, and continuously update their knowledge through lifelong learning. Key challenges in EBM integration include a lack of faculty training, limited curriculum time, and difficulties in accessing high-quality evidence. Overcoming these barriers requires structured EBM training, interdisciplinary collaboration, and the use of digital resources to facilitate evidence retrieval and application. By embedding EBM into medical education, institutions can equip future healthcare professionals with the skills necessary to provide high-quality, patient-centered care based on the latest scientific evidence